Overexpression of circulating CD38+ NK cells in colorectal cancer was associated with lymph node metastasis and poor prognosis - Wang, Xueling; Li, Haoran; Chen, Huixian; Fang, Kehua; Chang, Xiaotian (Frontiers in Oncology, 2024)
Introduction: Lymph node metastasis (LNM) is a critical prognostic factor for colorectal cancer (CRC). Due to the potential influence of immune system on CRC progression, investigation into lymphocyte subsets as clinical markers has gained attention. The objective of this study was to assess the capability of lymphocyte subsets in evaluating the lymph node status and prognosis of CRC. Methods: Lymphocyte subsets, including T cells (CD3+), natural killer cells (NK, CD3-CD56+), natural killer-like T cells (NK-like T, CD3+ CD56+), CD38+ NK cells (CD3-CD56+ CD38+) and CD38+ NK-like T cells (CD3+ CD56+ CD38+), were detected by flow cytometry. Univariate and multivariate analyses were used to assess the risk factors of LNM. The prognostic role of parameters was evaluated by survival analysis. Results: The proportion of CD38+ NK cells within the NK cell population was significantly higher in LNM-positive patients (p <0.0001). However, no significant differences were observed in the proportions of other lymphocyte subsets. Poorer histologic grade (odds ratio [OR] =4.76, p =0.03), lymphovascular invasion (LVI) (OR =22.38, p <0.01), and CD38+ NK cells (high) (OR =4.54, p <0.01) were identified as independent risk factors for LNM. Furthermore, high proportion of CD38+ NK cells was associated with poor prognosis of CRC patients (HR=2.37, p =0.03). Conclusions: It was demonstrated that the proportion of CD38+ NK cells was a marker overexpressed in LNM-positive patients compared with LNM-negative patients. Moreover, an elevated proportion of CD38+ NK cells is a risk factor for LNM and poor prognosis in CRC.